Process optimization of vacuum fried purple yam (Dioscorea alata L.) chips using response surface methodology - Tan, Mariel Adie P.; Rustia, Abigail S. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
This study aimed to optimize the process parameters of vacuum frying of purple yam chips using response surface methodology (RSM). Statistical models were generated that described the effects of time (9 to 15 min), temperature (88 to 108°C), and loading capacity (10 to 30%) during vacuum frying. The responses studied were color acceptability, texture acceptability, overall acceptability, moisture content, water activity, L* value, a* value, and b* value. The experimental results were fitted with a cubic equation using backward selection by a multiple regression analysis. The optimal conditions for vacuum frying of purple yam chips were determined to be a time of 9.44 min, temperature of 108°C, and 10% loading capacity, with desirability concept of 0.550. This combination of process parameters resulted to acceptable vacuum fried purple yam chips with desired color, texture, moisture content, (~2% d.b.), and water activity (~0.2). Verification experiments were conducted to measure the predictability of the models and the findings show that the models accurately predicted the responses.
Thesis Classification: P
Thesis (B.S. in Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Root crops -- Philippines -- Processing